ABSENCE OF THE REQUIREMENT OF MORAL ELIGIBILITY IN THE CANDIDATE FOR THE LEGISLATIVE ELECTIONS - Mohammed Ghatar Dayekh (Galaxy International Interdisciplinary Research Journal, 2023)
There is no doubt that most democratic people look at the legislative authority as a kind of holiness and respect, because of this constitutional institution with the role it plays and the possibility, rights and powers through which it is able to push the country forward or lead it backwards. One of the most important constitutional principles that the democratic state is keen to apply and adhere to its content in its general elections is to embrace the principle of freedom of candidacy, under which, The father of the competition to win the votes of the voters in front of the largest number of candidates for membership seats in the parliaments, but this does not mean in any way that the right to nominate is devoid of legal conditions that regulate it, and since the task of the deputy is more important and accurate than the task of the voter, and therefore it was natural that the conditions required by the legislator in the candidate are more severe than in the voter, that is, the candidate must be available to start The conditions of the voter, taking into account the strictness required by the legislator for the candidate, provided that he has moral competence, even if it is under different names such as, good character and commendable biography, or good reputation or good conduct within the conditions based on a rule that requires the legislator to be in the highest levels of morality.